The Effectiveness of Linguistics in Studying Fiscal and Monetary Policy Issues - Iskandarsyah Siregar (Budapest International Research and Critics University, 2022)
Linguistics is a branch of science that can maneuver to solve various problems. Linguistics succeeded in canceling the predicate given to laypeople, namely, linguistic science. Linguistics can even solve multiple disciplines, including fiscal and monetary policy issues. Fiscal and economic policies that require analysis of the past, present, and future phenomena can be answered immediately with a linguistic analysis knife. Critical discourse analysis is confidently taking action as a solution to this problem. The holistic interpretative approach used in this study tries to analyze the text by relating and relevant to the context and then abstracting it into a complete picture. This study succeeded in finding that critical discourse analysis can play a role in 3 things related to fiscal and monetary policy, namely: (1) text analysis is an analysis of linguistic elements in sentence construction used in formulating policies, (2) analysis of discourse practice is a background analysis behind the decision-makers who formulate policies and other situations and conditions behind the birth of business economic policies, and (3) analysis of socio-cultural and political is an analysis that is identifying the changes that occur as a result of these policies. This proves the effectiveness of Linguistics in studying fiscal and monetary policy issues.